Breck family correspondence and genealogical table
Correspondence (1780-1783) concerning the transfer of cargo and a bill of sale for goods belonging to the ship, Philippa, and a genealogical table of the Breck family (1949).
Photocopies.
Collection material in English.
Forms part of: Naval Historical Foundation collection.
Keywords: Philippa (Ship); Breck family; Ship's papers -- 18th century